Aphid Resistance: An Overlooked Ecological Dimension of Nonstructural Carbohydrates in Cereals - Sadras, Victor O.; Fereres, Elias; Borrás, Lucas; Garzo, Elisa; Moreno, Aranzazu; Araus, Jose Luis; Fereres, Alberto (Frontiers in Plant Science, 2020)
Nonstructural carbohydrates in cereals have been widely investigated from physiological, genetic, and breeding perspectives. Nonstructural carbohydrates may contribute to grain filling, but correlations with yield are inconsistent and sometimes negative. Here we ask if there are hidden functions of nonstructural carbohydrates, advance an ecological dimension to this question, and speculate that high concentration of nonstructural carbohydrates may challenge the osmotic homeostasis of aphids, thus providing a working hypothesis that connects nonstructural carbohydrates with aphid resistance in cereals. In the light of this proposition, the amount and concentration of nonstructural carbohydrates should be regarded as functionally different traits, with amount relevant to the carbon economy of the crop and concentration playing an osmotic role. We conclude with suggestions for experiments to test our hypothesis.